Analisis Tingkat Penerimaan Penggunaan Teknologi Informasi pada Usaha Mikro Kecil dan Menengah - Aswinanta, Asrul; Marliyah, Marliyah; Dharma, Budi (Journal of Business and Economics Research (JBE), 2025)
This study aims to measure how well the level of technology acceptance of Sipiongot Market MSME players is, and what variables affect it with the TAM Model approach. The research method used is quantitative by distributing questionnaires to 33 MSME owners. The results showed that X1, X2 and X3 against Y were 0.000 <0.05 and the calculated F value was 9.867> 2.71, so it can be concluded that there is an effect of perceived ease of use of social media (X1), perceived usefulness of social media (X2), and attitude towards using social media (X3) simultaneously affecting the intention to use social media (Y). However, X4 against Y is 0.187> 0.05 and t count 1.353 < t table 2.048, so it can be concluded that H4 is rejected, which means that there is no effect of actual social media use (X4) on intention to use social media (Y). Sipiongot Market MSMEs have a relatively good understanding of Social Media as a means of digital promotion. They report benefits such as: increasing operational efficiency, expanding market reach, facilitating communication, increasing sales, and supporting business development. In addition, MSME players consider the use of social media to be relatively easy because the interface is simple, easy to navigate and supports platform integration.